Waqf Implementation in Supporting SDGs-6 (Clean Water and Sanitation) at Salman Waqf Institution in Indonesia - Hisyam, Muhammad Ilham; Marwini (SMART Insight, 2024)
This research is motivated by the problems listed in the sixth Sustainable Development Goal (SDGs-6), namely related to the fulfillment of clean water and proper sanitation which is expected to be achieved by 2030, however this goal has not been achieved optimally until now. Beside that, the development of waqf in Indonesia has potential and contributes to addressing various socio-economic problems, including the provision of clean water and proper sanitation infrastructures. Salman Waqf Institution is one of the Waqf Institutions that is committed to overcome clean water and sanitation problems, both in Bandung city and other areas. This study aims to describe the form of waqf implementation in the provision of Clean Water and Proper Sanitation at Salman Waqf Institution and to review the SDGs-6 indicator targets from this implementation practice. This study used a qualitative method of field research with the case study of waqf institutions. Then analyzed descriptively using the Miles and Huberman models with the help of the NVivo 12 application. The results showed that there were several forms of implementation of waqf in support of SDGs-6, (1) Drinking Water Machines, (2) Drilling Wells (3) Toilet Washing Facilities (MCK), and (4) Piping. Then, it was also support for the global target 6.1 through the Ready-to-Drink Water Machine program, as well as the global target 6.2 through the MCK supply program, Clean Healthy Habits (PHBS) socialization, and providing convenience to vulnerable communities in accessing proper hygiene sanitation. With a strong institutional and partnership system, efforts to support SDGs-6 can be maximized so that the existing indicator targets can be achieved in 2030.